Duplication of a conserved mitochondrial enzyme gene arms parasitoid wasps with venom cytotoxicity and oogenesis regulation - Jiqiang Song; Zihan Qi; Chun He; Guilin Luo; Bo Yuan; Shan Xiao; Yi Yang; Fang Wang; Gongyin Ye; Qi Fang; Zhichao Yan (Proceedings of the National Academy of Sciences, 2025)
Gene duplication, followed by neofunctionalization, is a key mechanism driving the emergence of evolutionary novelties. Despite its significance, the molecular and functional processes underlying this phenomenon remain incompletely understood. By tracing the evolutionary history of cysteine-S-conjugate beta-lyase genes within the kynurenine aminotransferase family, we identified a gene duplication event in parasitoid wasps of the Chalcidoidea superfamily. Notably, a single-copy, highly conserved mitochondria-localized physiological gene underwent a significant duplication, resulting in one copy being recruited into the venom system and acquired cytotoxicity against wasps' hosts. Through this neofunctionalization process, we observed several key evolutionary changes, including loss of ancestral mitochondrial localization and enzyme activity, acquisition of a secretory signal peptide, shift in expression pattern, positive selection, and the establishment of evolutionary acquired protein–protein interactions. Additionally, we found that another duplicate copy was specialized in wasps' ovary and repurposed for oogenesis regulation. Our study offers a detailed insight into the genetic and molecular mechanisms that drive functional diversification during the evolution of gene families.